Jane Fonda at Watkins' Home re Campaign for Economic Democracy Fundraiser - Watkins, Howard::::::::: (1982)
Lois Lyness in purple top, Joe Floyd Asher in glasses, Tom Shilton, ?, Tony Correia with mustache, ?, Jane Fonda seated, Howard Watkins in dashiki, Randy Walsh playing guitar